RNA polymerase pausing at a protein roadblock can enhance transcriptional interference by promoter occlusion. Issue 9 (29th March 2019) - Hao, Nan; Crooks, Michael T.; Palmer, Adam C.; Dodd, Ian B.; Shearwin, Keith E.
Abstract : Convergent promoters exert transcriptional interference (TI) by several mechanisms including promoter occlusion, where elongating RNA polymerases (RNAPs) block access to a promoter. Here, we tested whether pausing of RNAPs by obstructive DNA‐bound proteins can enhance TI by promoter occlusion. Using the Lac repressor as a 'roadblock' to induce pausing over a target promoter, we found only a small increase in TI, with mathematical modelling suggesting that rapid termination of the stalled RNAP was limiting the occlusion effect. As predicted, the roadblock‐enhanced occlusion was significantly increased in the absence of the Mfd terminator protein. Thus, protein roadblocking of RNAP may cause pause‐enhanced occlusion throughout genomes, and the removal of stalled RNAP may be needed to minimize unwanted TI. Abstract :